THE BULGARIAN LEGAL FRAMEWORK DETERMINING THE SPECIFICITY OF PEDAGOGICAL WORK - Daniel Polihronov (Student Niepełnosprawny. Szkice i Rozprawy, 2023)
The article provides an overview of the legal framework that regulates the management, organisation and conduct of the educational process in the conditions of a pre-school multicultural environment. Basic legal provisions outlining the general rules for behaviour of subjects in the multicultural kindergarten’s educational process are presented.